2019
DOI: 10.1101/819029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circulating glutamine and Alzheimer’s disease: a Mendelian randomization study

Abstract: INTRODUCTIONAlzheimer’s disease is a devastating neurodegenerative disorder. Its worldwide prevalence is over 24 million and is expected to double by 2040. Finding ways to prevent its cognitive decline is urgent.METHODSA two-sample Mendelian randomization study was performed instrumenting glutamine, which is abundant in blood, capable of crossing the blood-brain barrier, and involved in a metabolic cycle with glutamate in the brain.RESULTSThe results reveal a protective effect of circulating glutamine (inverse… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…44,45 Imbalances of the glutamate-glutamine cycle can cause disturbances in sleeping patterns, mood, behavior, and amnesia, all of which are symptoms of AD. 46,47 In addition, several studies also suggested that glutamine supplementation should be beneficial for the prevention of cognitive decline. 46,48 Our findings suggested that genetically determined higher glutamine levels decrease the risk of AD in MR analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 Imbalances of the glutamate-glutamine cycle can cause disturbances in sleeping patterns, mood, behavior, and amnesia, all of which are symptoms of AD. 46,47 In addition, several studies also suggested that glutamine supplementation should be beneficial for the prevention of cognitive decline. 46,48 Our findings suggested that genetically determined higher glutamine levels decrease the risk of AD in MR analysis.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 In addition, several studies also suggested that glutamine supplementation should be beneficial for the prevention of cognitive decline. 46,48 Our findings suggested that genetically determined higher glutamine levels decrease the risk of AD in MR analysis. Additionally, further Phe-MR analysis confirmed the previously reported beneficial role of glutamine in the circulatory system.…”
Section: Discussionmentioning
confidence: 99%
“…择性 5-羟色胺再摄取抑制剂类抗抑郁药物(如氟西汀、帕罗西汀、西酞普兰等)两类。此 外,非药物治疗策略作为药物治疗的有效补充,一定程度上改善 AD 患者的-ABC‖症候群 [88] ,主要包括认知干预、BPSD 的非药物调控、日常生活能力训练、物理疗法,运动疗法、 传统医学以及照料者支持等 [78] [89] 。多中心横断面研究显示,早期营养筛查和更好 的营养护理可以降低营养不良发生率 [90] 。ESPEN 指南提出,应该对任何 65 岁以上老年人 进行营养风险筛查,尤其是同时存在衰弱、慢性非传染性疾病(如糖尿病、肿瘤等)、独 居、依靠社会服务或日常生活需要生活机构帮助的老年人以及住院患者 [91] 。对于认知障碍 究中的预测结果方面表现良好 [93,94] 。ESPEN 评估比较二者临床应用价值发现,MUST 与 ESPEN 营养不良定义标准有更好的相关性,即在风险筛查期间,MUST 可以更有效的识 别营养不良患者 [95] [94,96] 。其他营养风险筛查工具还包括营养不良筛查工具(malnutrition screening tool, MST)和短期营养评估问卷(short nutritional assessment questionnaire, SNAQ),它们在筛 查营养不良风险方面与 NRS-2002 具有相似的准确性 [97] 。主观总体评价(Subjective Global Assessment, SGA)、MNA 和老年营养风险指数(geriatric nutrition risk index, GNRI)是专 门为老年人开发的营养状况评估工具,且在大多数国家都得到了很好的验证 [98] 。对于痴呆 中晚期患者而言,如果存在主动进食障碍或 BPSD 所致进食行为异常,可以采用爱丁堡痴 呆进食评价问卷(Edinburgh feeding evaluation in dementia questionnaire, EdFED-Q) [99,100] 和进食行为评估量表(eating behavior scale, EBS)等工具评估以便协助决策进食和营养问 题 [101,102] [106] 。 研究显示,照料者具备营养相关任务的能力存在性别差异,即男性照料者与 AD 患者的较 低营养摄入有关 [107] 。前文所述的照料者负担与 AD 患者营养不良之间的恶性循环也提示 教育和协助照料者管理患者饮食摄入和营养补充的重要性。适宜的照料管理模式不仅可以 延缓痴呆患者病情进展、改善其生活质量,还可以减轻照料者负担 [108] 。对照料者或护理 人员进行培训和知识教育可能会对痴呆患者的营养行为和进食能力产生积极影响 [109,110] [111] 。⑤生活质量:如健康指数量表-5D 可作 为营养状况变化的非特异性粗略测量指标 [112] (图 1)。 [114,115] 。胰岛素管理海马等区域的葡萄糖代谢,并在直接调节 AD 早期记 忆受损相关激酶中发挥关键作用 [116] 。脑内胰岛素抵抗可出现营养分配中枢调控作用受损、 认知和情绪调节功能障碍以及大脑特异性神经退行性病变 [117] 。正因 AD 与糖尿病和胰岛 素抵抗相关认知损害具有共同的分子和细胞特征,近年来,有学者提出将 AD 视为-3 型糖 尿病‖,强调脑葡萄糖失调与 AD 发病机制间的联系 [118,119] [120] 。荟萃分析显示,3 种支链 AA(异亮氨酸、亮氨酸和缬氨酸)水 平下降与 AD 相关认知障碍风险升高有关 [121] 。随机对照研究表明,循环中谷氨酰胺及其 代谢产物可预防认知功能下降,在 AD 患者中起到保护作用 [122] 。然而,蛋白质/AA 摄入 在 AD 患者认知功能的作用机制不十分清楚,关于所需蛋白质最佳摄入量的研究证据十分 有限。一项近 1000 名受试者的大规模调查显示,高膳食蛋白质摄入量与非语言学习、语 言记忆以及 MCI 或 AD 风险减低呈正相关…”
Section: 食欲改变而影响摄食量;轻度痴呆阶段,因认知功能下降,患者忘记进食或准备食物能力 下降等导致营养摄入不足。随着疾病进展,患者出现各种 Bpsd,如淡漠使得食欲减退和unclassified
“…8 This approach is analogous to a randomized controlled trial and has become a powerful approach to assess the potential causal associations in recent years. 9,10 To comprehensively evaluate the associations between AiLD (including AIH, PBC and PSC) and the risk of cancer development and cancer-related death, we firstly conducted a systematic review and meta-analysis of cohort studies. Additionally, the two-sample Mendelian randomization analyses were conducted to confirm the associations with a p value of <.05.…”
Section: Introductionmentioning
confidence: 99%
“…Since the genotypes are presumed to be randomly allocated in the process of gamete formation, Mendelian randomization analysis is not affected by reverse causation and is less susceptible to confounding factors 8 . This approach is analogous to a randomized controlled trial and has become a powerful approach to assess the potential causal associations in recent years 9,10 …”
Section: Introductionmentioning
confidence: 99%